Clinical characteristics and outcomes in children hospitalised with pandemic influenza A/H1N1/09 virus infection – a nationwide survey by the Pediatric Infectious Diseases Group of Switzerland (Swiss Medical Weekly, 2015)
OBJECTIVE: To describe all patients admitted to children’s hospitals in Switzerland with a diagnosis of influenza A/H1N1/09 virus infection during the 2009 influenza pandemic, and to analyse their characteristics, predictors of complications, and outcome. METHODS: All patients ≤18-years-old hospitalised in eleven children’s hospitals in Switzerland between June 2009 and January 2010 with a positive influenza A/H1N1/09 reverse transcriptase polymerase chain reaction (RT-PCR) from a nasopharyngeal specimen were included. RESULTS: There were 326 PCR-confirmed patients of whom 189 (58%) were younger than 5 years of age, and 126 (38.7%) had one or more pre-existing medical condition. Fever (median 39.1 °C) was the most common sign (85.6% of all patients), while feeding problems (p = 0.003) and febrile seizures (p = 0.016) were significantly more frequent in children under 5 years. In 142 (43.6%) patients there was clinical suspicion of a concomitant bacterial infection, which was confirmed in 36 patients (11%). However, severe bacterial infection was observed in 4% of patients. One third (n = 108, 33.1%) of the patients were treated with oseltamivir, 64 (59.3%, or 20% overall) within 48 hours of onset of symptoms. Almost half of the patients (45.1%) received antibiotics for a median of 7 days. Twenty patients (6.1%) required intensive care, mostly for complicated pneumonia (50%) without an underlying medical condition. The median duration of hospitalisation was 2 days (range 0–39) for 304 patients. Two children (